Awareness of students in Saudi universities about creative accounting during 2021-2022 - Al-Amir, Saeed Ghazi Saeed AlHashimi; Baqader, Saleh Muhammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The current study aims to identify the extent of Saudi university students' awareness about creative accounting. To achieve the study's objectives, the researchers employed the descriptive analytical method, the social survey method, and the questionnaire to collect data from the study sample. This study was applied to a sample of (199) male and female Saudi university students. After collecting the data, the researcher utilized the Statistical Package for Social Sciences (SPSS) to analyze data. After analyzing the data, the researcher reached several results, the most important of which are: the presence of a high level of awareness among Saudi university students of the positive and negative effects of creative accounting and the presence of great effectiveness of the proposed methods from the researcher’s point of view to confront the risks and negatives of creative accounting, from the point of view of the study sample members with a relative weight reached 80.6%, There are statistically significant differences at the significance level (α ≤ 0.05) in the responses of Saudi university students about their awareness of creative accounting due to the gender variable in favor of males. In light of the results that have been reached, the researcher recommended some recommendations, the most important of which are: Creative accounting methods should be positively utilized to improve the quality of decision-making and to find practical solutions to the problems faced by companies. Instilling ethical discord among accountants, owners of companies, and various organizations and clarifying the consequences of financial manipulation and tax evasion, and enhancing the interest of Saudi universities in spreading the principles of creative accounting and raising awareness of its risks.
Keywords: Creative accounting; Accounting; Accounting Education